Exploring Hyperbolic Expressions in LANY's Album A Beautiful Blur - Maulani, Ully Indah; Prafitri, Wilma (Fakultas Ilmu Budaya Universitas Mulawarman, 2025)
This research analyzes the forms and meanings of hyperbolic expressions found in the lyrics of the album A Beautiful Blur by LANY. It employs a descriptive qualitative method with Claridge’s (2011) theory of hyperbole as the main theoretical framework, which categorizes hyperbole into seven forms such as single word hyperbole, phrasal hyperbole, clausal hyperbole, numerical hyperbole, the role of superlative, comparison, and repetition. The data were sourced from 13 songs on the album and collected through lyrical analysis. The study found data of hyperbolic expressions, divided into six forms, phrasal hyperboles, clausal hyperboles, single-word hyperboles, numerical hyperboles, comparison hyperboles, and the role of superlative. The findings of this research show that hyperbole in the lyrics of A Beautiful Blur serves as an effective expressive tool for conveying deep emotions. Moreover, the use of hyperbole in this album does not merely beautify the lyrics linguistically but plays a crucial role in reinforcing the emotional meanings conveyed, such as heartbreak, longing, uncertainty in love, and self-acceptance. The songwriter prefers a poetic approach to expressing emotions by using more than one word to create exaggerated effects that are not realistic but possess strong expressive power.Key Word: Expression, Figurative Language, Hyperbole, Lyric